UNVEILING MISCONCEPTIONS IN SCHOOL COUNSELING: EXPLORING STUDENT PERCEPTIONS AND CHALLENGES IN GUIDANCE SERVICES IMPLEMENTATION - Mahaly, Sawal; Hariko, Rezki; Syawaluddin; Makatita, Triandini (EDUCATIONE, 2025)
Guidance and counseling services play a crucial role in student development, yet misconceptions about their implementation persist. This study aimed to examine students' knowledge and misunderstandings regarding counseling services in schools, focusing on their perceptions of counseling roles and effectiveness. Using a quantitative descriptive approach, data were collected from 62 students of the FKIP Counseling Guidance Program at Pattimura University through a structured questionnaire. The results revealed significant misconceptions, with 75.81% of students believing that counseling is merely giving advice, 77.42% perceiving it as limited to certain students, and 74.19% viewing school counselors as "school police." Additionally, challenges in implementation, such as inadequate professional training, lack of stakeholder coordination, and low student engagement, were identified. The findings highlight the need for enhanced communication, targeted awareness campaigns, and structured professional development for school counselors. This research contributes to the literature by emphasizing the necessity of counselor training programs and improved collaboration within schools. Future studies should explore intervention strategies to address these misconceptions and examine their long-term impact on counseling effectiveness in educational settings.